Idly scribbling rhymers : poetry, print, and community in nineteenth-century Japan - Tuck, Robert, 1979- (Studies of the Weatherhead East Asian Institute, Columbia University., 2018)
"In Idly Scribbling Rhymers, Robert Tuck argues that Meiji era poetry played a significant role in the formation of ideas of national community, a function within literature usually ascribed solely to newspapers, novels, and literary journals. While the Meiji era saw a proliferation of these latter forms, traditional forms of poetry remained widely read, and important literary figures--including the most famous novelists and public intellectuals--wrote and published poetry. Tuck looks at traditional Japanese poetry not as something separate from the concerns of the new order, but rather as an integral part of both the emerging new forms of media and the emerging national consciousness. Tuck organizes his argument primarily (although not exclusively) around Masaoka Shiki. Shiki is known mostly for his haiku, but he wrote in all three major poetic genres, and worked for most of his career at the newspaper Nippon, one of Japan's most politically engaged and high minded metropolitan dailies. There has been no English language monograph focusing on Shiki"--